Imaging and Dosimetric Study on Direct Flat-Panel Detector-Based Digital Mammography System - Sharma, Reena (J Med Phys, 2018)
INTRODUCTION: Image quality of digital mammography system is generally defined by three primary physical parameters, namely, contrast, resolution, and noise. Quantification of these metrics can be done by measuring objective image quality parameters defined as contrast-to-noise ratio (CNR), modulation transfer function (MTF), and noise power spectra (NPS). MATERIALS AND METHODS: In the present study, various imaging metrics such as CNR, contrast detail resolution, MTF, and NPS were evaluated for a direct flat-panel detector-based digital mammography system following the European Guidelines. Furthermore, system performance relating to both image quality and doses were evaluated using figure of merit (FOM) in terms of CNR(2)/mean glandular dose (MGD) under automatic exposure control (AEC) and clinically used OPDOSE operating mode. RESULTS AND CONCLUSION: Under AEC mode, FOM values for the 4.5 cm thick BARC polymethyl methacrylate (PMMA) phantom were found to be 15.02, 15.88, and 19.82 at Mo/Mo, Mo/Rh, and W/Rh target/filter (T/F), respectively. Under OPDOSE mode, FOM values were found to 65.32, 11.80, and 1.14 for the BARC PMMA phantom thickness of 2, 4.5, and 8 cm, respectively. Under OPDOSE mode, the calculated MGD values for three Computerized Imaging Reference Systems slab phantoms having total thickness of 7 cm were observed to be 3.03, 2.32, and 1.75 mGy with glandular/adipose tissue compositions of 70/30, 50/50, and 30/70, respectively, whereas for the 2–8-cm thick BARC PMMA phantom, the calculated MGDs were found to be in the range of 0.57–3.32 mGy. All the calculated MGDs values were found to be lower than the acceptable level of dose limits provided in European Guidelines.